PERAN PENGENDALIAN EMOSIONAL ORANG TUA DALAM MEMBANGUN KESEHATAN MENTAL ANAK - Faliza; Usiono (Kampus Akademik Publiser, 2025)
Parental emotional control has an important role in building children's mental health. This research aims to examine how parents' ability to manage their emotions has an impact on children's psychological development. Good parental emotional control is able to create a stable, loving and emotionally safe family environment, which is an important foundation for children's mental health. Conversely, parents' inability to manage their emotions can cause stress in children, disrupt emotional development, and increase the risk of mental health problems, such as anxiety and depression. This research shows that parental emotional control is a crucial factor in supporting children's mental health and preventing psychological disorders in the future.